Non-Linear 3D Impedance Spectroscopy - Zamora, Martín Lucas (2014)
Non-linear Dielectric spectroscopy of Biological suspensions was first proposed by the Woodward and Kell group. The above mentioned arose as a technique able to monitor the enzymes state placed in the cell membrane of the biological tissue. This technique is limited to such enzymes because an external low frequency electrical field notably disturbs the membrane's electrical entourage. This kind of interactions can be monitor if the system generates current harmonics. This phenomenon was theorized by Astumian and Robertson. Treo, on his work suggests that the harmonics are originated at the interface and altered by the microorganism presence. Then Ruiz developed a fast method to detect the global non-linearity of a biological suspension. Nevertheless, on these works, the non-linearity interference due to the electrode-electrolyte interface was not controlled. The observed response is the result of the interface modulation because of the microorganism presence. On our work, we employed a tripolar measurement cell. The working electrode (WE) is a gold disc, the counter electrode (CE) is made of stainless steel and the reference electrode (RE) is a standard Ag/AgCl electrode. 1.74 g of lyophilized Saccharomyces cerevisiae was dissolved in 90 ml of saline medium. A frequency (0.1 - 1000 Hz) and tension AC (0- 600 mV) sweep was carried out without DC polarization. The first 5 output current harmonics were monitored. Results would indicate that it was successfully possible to measure the non-linearity due to only the yeasts cells, without the non-linear interference of the electrode - electrolyte interface.